Efficacy and safety of vedolizumab for pediatrics with inflammatory bowel disease: a systematic review - Shengbo Fang; Yanqing Song; Chunyan Zhang; Libo Wang (BMC, 2022)
Abstract Background Vedolizumab use in pediatrics is still off-label and the data are limited. We conducted a systematic review evaluating the efficacy and safety of vedolizumab in children and adolescents with inflammatory bowel disease (IBD). Methods PubMed, EMBASE and Cochrane databases were systematically searched for studies of vedolizumab in children and adolescents with IBD reporting clinical remission, response, corticosteroid-free (CS-free) remission, mucosal healing, or safety up to December 3rd 2021. Results Ten studies, comprising 455 patients were included. For CD, the pooled clinical remission rates were 25% (19/75) at 6 weeks, 28% (25/85) at 14 weeks, 32% (17/53) at 22 weeks, and 46% (43/92) at 1 year. For UC/IBD-U, the pooled clinical remission rates were 36% (25/70) at 6 weeks, 48% (52/101) at 14 weeks, 53% (24/45) at 22 weeks, and 45% (50/112) at 1 year. Mucosal healing was found in 17%-39% of CD and 15%-34% of UC/IBD-U respectively. Six percent of patients reported serious adverse events. Conclusions According to low-quality evidence based on case series, approximately one-third and one-half of patients for CD and UC/IBD-U respectively achieved remission within 22 weeks, and about half of patients achieved remission at 1 year with reasonable safety profile. Long-term benefit profile data and high quality evidence are still needed.